Ontology merging using belief revision and defeasible logic programming - Gómez, Sergio Alejandro (2012)
We combine argumentation, belief revision and description logic ontologies for extending the -ontologies framework to show how to merge two ontologies in which the union of the strict terminologies could lead to inconsistency. To solve this problem, we revisit a procedure presented by Falappa et al. in which part of the o ending terminologies are turned defeasible by using a kernel revision operator.